Imbalance identity in E-sports news intersectionality on Covid-19 pandemic situation - Marta, R. F.; Prasetya, A. A.; Laurensia, B.; Stevani, S.; Syarnubi, K. L. (Jurnal ASPIKOM, 2020)
The COVID-19 situation is a moment that homogenizes everyone's efforts to reduce outdoor activities, so a space of self-actualization is required to trigger creative skills and sportsmanship. The most qualified alternative to answer these needs for everyone in the digital age is the E-sport. Trying to take advantage of this opportunity, Bubu Gaming, as an Indonesian digital sports games marketer, initiated "LiveStream Aid 2020" with the theme "PlayFromHome, Stay Safe, Donate." Tirto.id and Kompas.com covered the two-day event. However, researchers interrogate those two news frames and discover different perspectives. Guided by Entman Framing Analysis with the theory of intersectionality, the results obtained indicate the imbalance of identity in those news frames. Tirto.id viewed from the category of structural intersectionality and built the reader's opinion that the government, through Sandiaga Uno, supports these activities. On the other hand, Kompas.com put the name of Pevita Pearce without adequate narrative so that it can be categorized as representational intersectionality.